1997
DOI: 10.1128/aac.41.9.1859
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anti-Toxoplasma activity of SDZ 215-918, a cyclosporin derivative lacking immunosuppressive and peptidyl-prolyl-isomerase-inhibiting activity: possible role of a P glycoprotein in Toxoplasma physiology

Abstract: The immunosuppressive agent cyclosporin A (CsA) also possesses broad-spectrum antimicrobial activity. Previous investigators have reported that the obligate intracellular protozoan Toxoplasma gondii is sensitive to CsA. We have measured the sensitivity of Toxoplasma to 26 CsA derivatives that maintain only a subset of the parent compound's activity. We identified one compound, SDZ 215-918, that is a particularly potent inhibitor of parasite invasion and replication, with a 50% inhibitory concentration of 0.45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…26 In our study, H-7-94 and F-7-62 CsA derivatives, have strongly bound to TcCyP19 but both compounds proved to exhibit a negligible immunosuppressive activity, 11 unlike CsA and other CsA analogs, which showed a physical and functional interaction with calcineurin, suppressing IL-2 gene expression.…”
Section: The Percentage Of Infection Inhibition Was Calculated As [(Ementioning
confidence: 88%
“…26 In our study, H-7-94 and F-7-62 CsA derivatives, have strongly bound to TcCyP19 but both compounds proved to exhibit a negligible immunosuppressive activity, 11 unlike CsA and other CsA analogs, which showed a physical and functional interaction with calcineurin, suppressing IL-2 gene expression.…”
Section: The Percentage Of Infection Inhibition Was Calculated As [(Ementioning
confidence: 88%
“…Previous studies based on efflux analyses in the presence of P-gp inhibitors suggested that an active P-gp homologue is present in T. gondii [6], [7]. Recently, two P-gp homologues with the typical P-gp structure have been identified in the genome of the parasite (TgABC.B1 and TgABC.B2) and found to be constitutively expressed in both the vegetative and quiescent stages of T. gondii 's life cycle [8].…”
Section: Introductionmentioning
confidence: 99%
“…Further molecular characterization revealed that TgABC.B1 is coded by a single copy gene, expressed as a membrane-associated protein of ∼150 kDa, and constitutively present in different parasite strains [9]. Indications that T. gondii P-gp may be involved in key biological processes, such as replication and host cell invasion were provided by early works using P-gp inhibitors [6], [10]. However, given that these studies used host cells containing P-gp, it was not possible to discriminate between the contribution of T. gondii and host cell P-gp.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that anti-parasitic activity of CsA could be due to its binding to other targets such as P-glycoprotein (P-gP), in which the some CsA analogues proved to be potent modifiers of its activity [123,137,142]. It was suggested, however, that calcineurin was the target of CsA complexed to the cytosolic cyclophilin expressed in E. histolytica [140].…”
Section: Cyclophilins Intra-cellular Signaling and Development Of Camentioning
confidence: 99%